Implementasi Program Keluarga Harapan Dalam Meningkatkan Kesejahteraan Masyarakat Miskin - Muhammad Daud; Yushita Marini (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2018)
The government has done its best to solve cases of poverty in Indonesia. However, the efforts made by the government have been implemented but the government has not been able to complete optimally and thoroughly and prosper the Indonesian people, this becomes a prolonged problem. In this case the government issued Keluarga Harapan Program (PKH). Implementation of PKH program located in Kajhu village, Baitussalam sub district, Aceh Besar district due to Rumah Tangga Sangat Miskin (RTSM) so this should get special attention from the government. The method used in this research is qualitative method with descriptive research type. The results of the research say that PKH is able to eradicate poverty in Kajhu village and able to bring prosperity to the community, so that the community is very grateful for the existence of this PKH in the village, and reduce the existing poverty. Obstacles obtained are the manipulation / forgery of data by people who are not entitled to receive PKH funds.